2012
DOI: 10.1111/j.1365-2966.2012.20411.x
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of stars around spiral arms

Abstract: Spiral density wave theory attempts to describe the spiral pattern in spiral galaxies in terms of a long-lived wave structure with a constant pattern speed in order to avoid the winding dilemma. The pattern is consequently a rigidly rotating, long-lived feature. We run N-body simulations of a giant disc galaxy consisting of a pure stellar disc and a static dark matter halo, and find that the spiral arms are transient features whose pattern speeds decrease with radius, in such a way that the pattern speed is al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
185
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 47 publications
23
185
1
Order By: Relevance
“…They show clearly in their simulations that the radial migration acts to maintain the negative radial metallicity gradient but significantly broadens the metallicity distribution at every radius by about 0.8 dex (see Figure 2 in Grand & Kawata 2015). The motion of star clusters in spiral arms and the angular momentum exchange is similar to that of stars investigated in simulations of stellar discs (Fujii & Baba 2012;Grand et al 2012).…”
Section: Computation Of Oc Birth-sitesmentioning
confidence: 69%
“…They show clearly in their simulations that the radial migration acts to maintain the negative radial metallicity gradient but significantly broadens the metallicity distribution at every radius by about 0.8 dex (see Figure 2 in Grand & Kawata 2015). The motion of star clusters in spiral arms and the angular momentum exchange is similar to that of stars investigated in simulations of stellar discs (Fujii & Baba 2012;Grand et al 2012).…”
Section: Computation Of Oc Birth-sitesmentioning
confidence: 69%
“…On the other hand, the power spectrum of simulation G13F (and to an extent G14) shows evidence of a turnover in power on scales of k ∼ 0.4 km s −1 , which is the characteristic feature of the observed power spectrum. Therefore, it is possible that the main features of the observed power spectrum can be explained purely by the systematic stellar motion induced by co-rotating spiral arms seen in simulations (e.g., Grand et al 2012aGrand et al ,b, 2014. We note that this study is limited to our current set of simulations, and we have not extensively searched for a N -body simulation model with transient spiral arms only that can better reproduce the observed power spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…It was not until the work by Sellwood & Binney (2002) that radial migration was established as an important process affecting the entire disc, where stars shift guiding radii due to interaction with transient spiral structure. A number of works using N-body and N-body/SPH simulations (e.g., Grand et al 2012;Minchev et al 2011;Roškar et al 2008) have confirmed that migration always takes place in numerical galactic discs.…”
Section: Radial Migrationmentioning
confidence: 99%